RANCANG BANGUN ALAT PEMANTAU DENYUT JANTUNG DAN SUHU TUBUH BERBASIS MIKROKONTROLER MENGGUNAKAN LABVIEW DI KLINIK TAZAKKA PURWAKARTA - Dede Irmayanti; Mochammad Imam Sulistiyo Sarjowo; Minarto, Minarto (Jurnal Teknologika, 2023)
Heart rate and body temperature are one of the determining factors or vital signs in the selection of health. Measurements regarding heart and body temperature are carried out to determine the clinical signs and are useful to confirm the diagnosis of a disease. In the process of checking the heart rate and body temperature still use conventional equipment such as a stethoscope and glass thermometer. The measurement process is done one by one then the process of recording the results of measurements is done by hand. this system is less effective because it takes a lot of time. In this study a monitoring system was developed that refutes the state of integrated body temperature, the measurement results related to the patient's health status installed through a desktop-based application. This monitoring process is carried out using a heart rate sensor to deny the heart rate and a DS18B20 sensor to measure body temperature. Input data processing from the second sensor is done using a microcontroller. The method used to make this research is a prototype. Overall this system is able to measure heart rate and body temperature, equipped with a user interface feature using LabView that can display heart rate, body temperature and to find out the level of health from the research results obtained an error value of 2.26% to measure heart rate and 0.81% for body temperature measurements. Keywords: Heart Rate, Body Temperature, Automation System, Information System, LabView